2019
DOI: 10.1073/pnas.1806790116
|View full text |Cite
|
Sign up to set email alerts
|

Limits of multifunctionality in tunable networks

Abstract: SignificanceFunctionally optimized networks are ubiquitous in nature, e.g., in allosteric proteins that change conformation upon binding to a ligand or vascular networks that distribute oxygen and nutrients in animals or plants. Many of these networks are multifunctional, with proteins that can catalyze more than one substrate or vascular networks that can deliver enhanced flow to more than one localized region of the network. This work investigates the question of how many simultaneous functions a given netwo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 49 publications
1
57
1
Order By: Relevance
“…As in Ref. [5], we find power-law scaling: N c T ∼ N γc and w ∼ N γw with γ c ≈ γ w ≈ 0.7 for β = 0. As we increase β, γ c and γ w increase, saturating to unity (insets to Fig.…”
Section: Tuning Of Flow Networksupporting
confidence: 86%
See 1 more Smart Citation
“…As in Ref. [5], we find power-law scaling: N c T ∼ N γc and w ∼ N γw with γ c ≈ γ w ≈ 0.7 for β = 0. As we increase β, γ c and γ w increase, saturating to unity (insets to Fig.…”
Section: Tuning Of Flow Networksupporting
confidence: 86%
“…Here we study two systems with rough landscapes (Fig. 1), namely tuned flow networks [5] and sphere packings [1,2,20]. In both systems, we show that we can smooth out local minima, increasing the ability to reach global minima.…”
Section: Introductionmentioning
confidence: 82%
“…The effect of bond removal on the elastic properties of spring networks has also been investigated in the context of material science [ 42 ]. It has been further demonstrated that tuning based on adding or removing links can be employed to generate networks which display multifunctional responses [ 43 ]. Yan et al considered 2D on-lattice models which evolve under the swapping of springs to accomplish an allosteric task [ 19 ], and deduced design and physical aspects in emerging functional networks.…”
Section: Models Of Allosteric Protein Machinesmentioning
confidence: 99%
“…directly to allostery in a protein. 86,87 After applying a 12 Å distance cut-o↵ to the derivative edge metric, contacts at the HisF-HisH interface are highlighted. A structural representation of the edges with large magnitude derivative values from Equation 5 is provided in Figure 4A.…”
Section: Derivative Centrality Metric Of Hessianmentioning
confidence: 99%